Accurate Underground Wireless Ranging and Tracking - M Hedley (The Australasian Institute of Mining and Metallurgy, 2011)
Tracking plant and personnel in underground environments provides multiple potential benefits for a mine including increasing safety, better monitoring of production, traffic control, and in the future monitoring and control of autonomous vehicles. The main techniques for wireless tracking are to use radio frequency identification (RFID), signal strength based techniques, and time of arrival (TOA) based techniques. RFID does not provide continuous tracking and signal strength techniques have poor accuracy in the complex radio propagation environment present in mines. TOA based techniques are potentially the most accurate, but most current equipment does not realise the potential of the technique. CSIRO has been developing the wireless ad-hoc system for positioning (WASP) system for wireless tracking in a range of challenging environments including underground mines. WASP has been licensed for sporting applications and has delivered encouraging results in early trials for a surface and an underground mining application. The system utilises a number of ‘anchor nodes’ that are placed at surveyed fixed locations within the mine, and tags attached to plant or personnel to be tracked. The system provides an ad hoc data communication network, thus wired data connections are not required to the anchor nodes. WASP uses transmissions in the 5.8 GHz ISM (instrumentation, scientific and medical) frequency spectrum to perform highly accurate ranging between nodes, hence tracking of tags. The localisation performance of the system depends upon the radio propagation environment, ranging from 0.1 m in low multipath conditions. In this paper we describe the WASP system and provide results of initial testing in an underground mine that shows that the system achieves high ranging accuracy, hence localisation accuracy.